Extended micromagnetic model for the detection of superparamagnetic labels using a GMR vortex sensor - Wetterau, Lukas; Abert, Claas; Suess, Dieter; Albrecht, Manfred; Witzigmann, Bernd (Journal of Physics Communications, 2021)
A self-consistent micromagnetic model is proposed for simulating interactions between a superparamagnetic label particle and a low-noise GMR vortex sensor, focusing on most common operations such as label detection and saturation. For this purpose, we evaluate the combined action of vortex stray field and the applied external field. By solving the Landau-Lifshitz-Gilbert equation we find that a superparamagnetic label with a diameter of 60 nm can be successfully detected by a magnetic vortex structure assisted with an external magnetic field of 100 mT. Subsequently, the self-consistent spin diffusion model is applied to calculate electric response of a standard low-noise GMR vortex sensor to the presence of magnetically-saturated label. It is shown that the stray field of the activated label produces a detectable potential difference in the GMR sensor of 27.1 to 27.8 mV, the magnitude of which depends on location of the label with respect to the sensor surface.
CRIS-Team WoS Importer:2021-08-13